Analisis Kointegrasi Zakat dan Pertumbuhan Ekonomi Indonesia Periode Tahun 2015-2018 - Tambunan, Khairina; Harahap, Isnaini; Marliyah, M. (IAIN Kudus, 2019)
This study analyzes the existence of short-term and long-term relationships between zakat variables and Indonesia's economic growth in the 2015-2018 period. Zakat as one of Islamic philanthropy is used to prosper Muslims. Zakat is divided into productive zakat and consumptive zakat. This study uses a cointegration test which is one of the tests of the VAR VECM method to determine whether or not there are short-term and long-term effects. The data used uses time-series data from 2015-2018 with data interpolated to monthly period data. The results show that zakat affects Indonesia's economic growth both in the short and long term.